Supera-Héroe vs. Supera hombre : Análisis de la mitología de héroes y sus discursos en el siglo xx - Moreano Recalde, Ramón Gerónimo (2014)
The topic to treating itself comes across several fields, all of them linked to the culture of masses, by it emphasis is tried to put in the analysis of the relation of this type of culture by the thought, by the instruments of power, and principally by the communication of masses. All that having in it counts the superheroes as reference of analysis. In the first instance the principal characteristics of a superhero are analyzed, not only what makes them be as such, but in addition the whole ideological and political context. An important point that is analyzed, they are the principal types of moral behaviors of the superheroes and his relation with some social rules, besides which the degree allows to see ideological manipulation that is given concerning them.